Chapter 10 Lifting the Veil Voices, Visions, and Destiny in Malory's Morte Darthur - Saunders, Corinne (Boydell & Brewer, 2018)
Always rewriting and always rewritten, romance also opens onto new ways of seeing. Romance retains its power in part because, in its engagement with thinking, feeling, and being in the world, it continues to allow readers to re-vision themselves. Medieval depictions of the continuum of mind and body, the role of affect in cognition, and the physical effects of love, loss, and trauma can have powerful resonances for modern readers.